Film and Video Analysis in the Digital Humanities – An Interdisciplinary Dialog - Burghardt, Manuel; Heftberger, Adelheid; Pause, Johannes; Niels-Oliver Walkowski; Zeppelzauer, Matthias (Digital humanities quarterly, 2020)
This editorial introduces the special issue on “Digital Humanities & Film Studies: Analyzing the Modalities of Moving Images,” which contains a total of eight exciting contributions. Moreover, this editorial aims to highlight the complementary disciplinary perspectives on the computer-aided analysis of moving images, which are important prerequisites to better understand and situate a common DH perspective